TECHNO-ECONOMIC UTILIZATION COMPLETE FEED FOR BEEF CATTLE DEVELOPMENT IN INDONESIA - Limbang Kustiawan Nuswantara; Bambang Waluyo Hadi Eko Prasetiyono; Agus Setiadi (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2023)
Complete feed is very crucial for cattle development in Indonesia. This study analyzed the technical and economical use of complete feed from agricultural waste to developing beef cattle in Indonesia. Agricultural waste is arranged into a complete feed based on crude protein and total digestible nutrients. Experimental research and survey research was used in the study. Experimental research used five feeds, namely T0 (feed usually given by farmers), T1 (12% CP, 60 TDN), T2 (12% CP, 63% TDN), T3 (12% CP, 66% TDN), T4 (12% CP, 69% TDN). The technical parameters observed were dry matter digestibility, organic matter digestibility, rumen VFA, and rumen NH3. Data analysis uses Analysis of Variance (ANOVA), and if there is a difference, it is continued with the Duncan Multiple Range Test (DMRT). The economic analysis is revenue, feed costs, and income over feed cost (IOFC). Survey research was conducted on ten beef cattle farmers to analyze the differences between farmers who used complete feed and those who did not. The results showed a difference between complete feed T1-T4 and feed T0 (control). The T3 feed (12% CP, 66% TDN) yielded the best results. Farmers who use complete feed show higher yields compared to farmers who do not use complete feed. Fattening beef cattle with a total of 10 heads with a rearing period of 90 days produced was Rp 9,100,000 with an R/C ratio was 1.05. The conclusion from this study is that using complete feed from agricultural waste can increase the income of beef cattle farmers. This complete feed can be recommended for developing beef cattle in Indonesia.